Graph-based search procedure for vector autoregressive models - Alessio Moneta; Peter Spirtes (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2005)
In this paper we present a semi-automated search procedure to deal with the problem of the identification of the causal structure related to a vector autoregressive model. The structural form of the model is described by a directed graph and from the analysis of the partial correlations of the residuals the set of acceptable causal structures is derived.
Keywords: 330; VAR-Modell